A RESEARCH ON CONSUMER PERCEPTIONS TOWARDS PACKAGING IN THE SHOPPING PROCESS - ÖZKAYA, BETÜL; ENE, SELDA (My University, 2018)
Consumer perceptions, which are influenced by environmental factors such as personal, store environment and merchandising presentation techniques, are influencing consumer behaviors and purchasing decisions in many respects. One of the elements of visual presentation that can affect consumer perceptions and have a positive effect on consumer behavior is also packaged in the store environment. Product packaging, as well as the competitive advantage to retailer businesses with many elements such as brand awareness, image, product information and quality, transport and storage facilities offered to benefits consumers. Retailer businesses that want to show success in a highly competitive environment be able to influence consumer behavior positively with visual presentations and packaging etc. elements and retailers will meet consumer expectations of innovation. At this point, consumers will be able to increase the amount of purchases and the frequency of purchases. In the study, the relationship between consumers of packaging and novelty expectations and purchasing frequency was examined in the shopping process from retailer stores in shopping centers in Turkey. It was aimed to give more importance to the consumer perceptions of packaging and innovative expectations for national and international retail enterprises with the study results.

Gerek kişisel, gerekse mağaza içi yerleşimi ve sunum teknikleri gibi faktörlerin etkisinde oluşan tüketici algıları birçok bakımdan tüketici davranışlarını ve satın alma kararlarını etkilemektedir. Mağaza ortamında, tüketici algılarını etkileyebilecek ve tüketici davranışlarında olumlu etki yaratacak görsel sunum unsurlarından biri de ambalajlamadır. Perakendeci işletmelere sağladığı rekabet avantajının yanı sıra ürün ambalajları, marka farkındalığı, imajı, ürün bilgisi ve kalitesi, taşıma ve saklama kolaylıkları vb. gibi birçok unsuru ile de tüketicilere faydalar sunmaktadır. Yoğun rekabet ortamında başarı sağlamak isteyen perakendeci işletmeler görsel sunumları, ambalaj vb. gibi unsurları ile tüketici davranışlarına olumlu yönde etki edebilecekler ve tüketicilerin yenilik beklentilerini karşılayacaktır. Bu sayede tüketicilerin satın alma miktarını ve satın alma sıklığını arttırabileceklerdir. Çalışmada, alışveriş merkezlerinde dolaşan, perakendeci mağazalardan alışveriş yapan tüketicilerin ambalaja yönelik algıları ile yenilik beklentileri ve satın alma sıklıkları arasındaki ilişki incelenmiştir. Çalışma sonuçlarının, ambalaja verilen önemin artmasını sağlayacağı düşünülmektedir. Ulusal ve uluslararası perakende işletmelerin ambalaja yönelik tüketici algılarına ve yenilikçi beklentilerine verdikleri önemin artması amaçlanmaktadır.
ALIŞVERİŞ SÜRECİNDE AMBALAJA YÖNELİK TÜKETİCİ ALGILARI ÜZERİNE BİR ARAŞTIRMA